Regulation of intestinal guanylate cyclase by the heat-stable enterotoxin of Escherichia coli (STa) and protein kinase C. - Crane, J K (1992)
The heat-stable enterotoxin of Escherichia coli (STa) stimulates membrane-bound guanylate cyclase in intestinal epithelium and induces fluid and ion secretion. Using the T84 human colon carcinoma cell line as a model, we observed that phorbol esters markedly enhanced STa-stimulated cyclic GMP accumulation in T84 cells (C. S. Weikel, C. L. Spann, C. P. Chambers, J. K. Crane, J. Linden, and E. L. Hewlett, Infect. Immun. 58:1402-1407, 1990). In this study we document that the phorbol ester treatment increases 125I-STa-binding sites as well as membrane-bound guanylate cyclase activity in T84 cells and provide evidence that both effects are mediated by phosphorylation. Guanylate cyclase activity was increased approximately 50% in membranes prepared from intact T84 cells treated with phorbol-12,13-dibutyrate (beta-PDB) and after treatment of homogenates with beta-PDB in a manner dependent on ATP, MgCl2, and cytosol. Similarly, treatment of membranes with purified bovine brain protein kinase C in the presence of appropriate cofactors and beta-PDB resulted in an increase in STa-stimulated guanylate cyclase activity of about 70%. Likewise, the number of 125I-STa-binding sites was increased by about 25 to 40% in membranes prepared from intact cells or homogenates treated with beta-PDB; no effect on binding affinity (Kd = 0.15 nM) was noted. These experiments suggest that protein kinase C may phosphorylate the STa receptor-guanylate cyclase or a closely related protein and increase guanylate cyclase activity. The stimulatory effects of protein kinase C on STa-sensitive guanylate cyclase are opposite in direction to the profound inhibitory effects of the kinase on atrial natriuretic peptide-stimulated guanylate cyclase, demonstrating differential regulation by protein kinases within the guanylate cyclase-receptor family.